Market access by smallholder farmers in Malawi: implications for technology adoption, agricultural productivity, and crop income - Zeller, Manfred; Diagne, Aliou; Mataya, Charles (International Food Policy Research Institute, 1997)
In Malawi, maize is the major crop and food staple. Given limited off-farm employment opportunities, much-needed increases in household income for improving food security must come from gains in agricultural productivity through better technology and more profitable crops. In the past, agricultural policy promoted hybrid maize and, more recently, tobacco to increase smallholder income. This paper presents an analysis of what determines the adoption of these two crops and what kind of income effects follow from adoption. Apart from factor endowment and exposure to agroecological risks, differences in the household's access to financial and commodity markets significantly influence its cropping shares and farm income.